2017
DOI: 10.1371/journal.ppat.1006541
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 epitopes presented by MHC class I types associated with superior immune containment of viremia have highly constrained fitness landscapes

Abstract: Certain Major Histocompatibility-I (MHC-I) types are associated with superior immune containment of HIV-1 infection by CD8+ cytotoxic T lymphocytes (CTLs), but the mechanisms mediating this containment are difficult to elucidate in vivo. Here we provide controlled assessments of fitness landscapes and CTL-imposed constraints for immunodominant epitopes presented by two protective (B*57 and B*27) and one non-protective (A*02) MHC-I types. Libraries of HIV-1 with saturation mutagenesis of CTL epitopes are propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…We first examined several well-characterized epitopes presented by the protective HLA alleles B*57 (KF11 [position 162 to 172] and TW10 [position 240 to 249]) and B*27 (KK10 [position 263 to 272]) and observed that mutations in these epitopes led to greater loss of viral fitness than in the epitopes presented by the nonprotective HLA allele A*02 (SL9 [position 77 to 83]) ( Fig. 3A ) ( 37 , 38 ). Furthermore, we ranked MHC-I alleles by the ratio of their prevalence in HIV controllers to their prevalence in progressors based on The International HIV Controllers (TIHIVC) study ( Table S3 ) ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We first examined several well-characterized epitopes presented by the protective HLA alleles B*57 (KF11 [position 162 to 172] and TW10 [position 240 to 249]) and B*27 (KK10 [position 263 to 272]) and observed that mutations in these epitopes led to greater loss of viral fitness than in the epitopes presented by the nonprotective HLA allele A*02 (SL9 [position 77 to 83]) ( Fig. 3A ) ( 37 , 38 ). Furthermore, we ranked MHC-I alleles by the ratio of their prevalence in HIV controllers to their prevalence in progressors based on The International HIV Controllers (TIHIVC) study ( Table S3 ) ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…HLA alleles associated with HIV control impart thymic selection for TCR repertoires with increased HIV recognition and variant cross-reactivity 65 . Although differential TCR usage alone is insufficient to explain spontaneous control or confer functional differences in CD8 + T cells [66][67][68] , cross-reactive TCRs have been shown to limit viral escape pathways in controllers, consistent with the findings that mutations within epitopes targeted predominantly by controllers are poorly tolerated due to impaired viral replication 69,70 and that their recognition is maintained in controllers by cross-reactive TCRs and de novo responses [71][72][73] .…”
Section: Cd8 + T Cell Specificity In Spontaneous Hiv Controlmentioning
confidence: 66%
“…The modest polymorphism observed for topologically important epitopes that precludes them being classified as exact matches in HIV-1 M group is likely the result of their underlying immunogenicity, which we observed in this study. Moreover, mutations within highly networked epitopes have been shown to impair viral fitness, so these responses may be effective in mediating immune control despite mutational changes [9, 5254]. The finding that the networked epitopes were targeted more robustly than the Epigraph peptides and show evidence of some sequence variation likely indicates that these are more immunogenic in vivo , and that these topologically important regions would indeed be represented as part of the peptide repertoire presented on the infected target cells.…”
Section: Discussionmentioning
confidence: 99%